2018
DOI: 10.1155/2018/3757083
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Affective User-Centered Design of Video Games Using Qualitative Methods

Abstract: In recent years, researchers and practitioners in the human-computer interaction (HCI) community have placed a lot of focus in developing methods and processes for use in the gaming field. Affective user-centered design (AUCD) plays an important role in the game industry because it promotes emotional and mental communication, hence improving the interaction modes between users and video games. This paper looks at the development of a suitable AUCD guideline to determine if the expressed emotion, semantics, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…Indeed, students gave the game a higher score for usefulness than for entertainment. In any case, in future studies it would be interesting to examine this point further, perhaps resorting to a qualitative methodology that could provide more information on the opinion of the participants related to these aspects [29].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, students gave the game a higher score for usefulness than for entertainment. In any case, in future studies it would be interesting to examine this point further, perhaps resorting to a qualitative methodology that could provide more information on the opinion of the participants related to these aspects [29].…”
Section: Discussionmentioning
confidence: 99%
“…So, for the game industry, usability is essential, but not sufficient to assess the user experience of a product as a whole, since it deals with pleasure and emotions, or, in other words, with affect [3]. By observing the list proposed by Ng et al [1] shown in the left column of Table 1, it is reasonable to say that much of the subjective experience from games is based on options, i.e., features whose usage can be customized or measured in some way. Thus, the players' choices, both before and during the game, can be monitored in background so it does not interrupt the game's flow.…”
Section: Methodsmentioning
confidence: 99%
“…It is an automatic in-background track of players' actions and reactions in a gaming experience towards several options and situations deliberately added to it. The idea is to evaluate ten groups of five individuals, divided per age range and gender, in order to learn each audience's behaviors and preferences on the affective game design components highlighted in [1], through purely numerical indicators from within the videogame, with no human observation, as in the related works, nor bio-signal processing. The game for the playtest is yet to be designed, but due to artistic limitations and in order to comprehend the metrics proposed here, it will probably be a short 2D-RPG-adventure game.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrera et al [42] used fivechannel EMOTIV and participants played the video game Call of Duty, which aimed to provide an early insight into how playing a video game with an EEG-based BCI would impact a participant's mood as compared with a traditional video gaming setup. Commercial video games have been used to analyse emotions, including Little Big Planet2 [43], Counter Strike [32], DX-Ball [36] and Quaker3 Arena [44].…”
Section: Introductionmentioning
confidence: 99%